PSYCHOEDUCATION FOR PSYCHOTIC PATIENTS - Prasko, Jan; Vrbova, Kristyna; Latalova, Klara; Mainerova, Barbora (Biomedical papers, 2011)
Background: Psychoeducation programs have been shown in the last two decades to significantly improve the post-hospital discharge care of individuals with schizophrenia by demonstrated effects on rehospitalization rates, compliance with medication and knowledge. The benefits of psychoeducation can be sustained for up to seven years although most studies have not shown such enduring benefit. Psychoeducation is a type of psychotherapeutic support that aims to provide broad and adequate information on psychotic disorders for both patients and their families.Method: The purpose of the group psychoeducational program at the Psychiatric clinic in Olomouc is to familiarize patients with the core of the disorder, explain the part played by pharmacotherapy, teach recognition of the warning signs of relapse, to advise on communication problems within families, and finally the training of social skills.Results: Patients perceive the program as meaningful and helpful in better understanding their lives.
Keywords: Group psychoeducation/Psychosis/Schizophrenia